Iterative development of engineering in school teaching capacities in Danish primary and lower secondary schools. - Peer Schrøder Daugbjerg; Martin Krabbe Sillasen (European Teacher Education Network, 2019)
We have developed and performed a Teacher Professional Development (TPD) programme for introducing and implementing engineering in primary and lower secondary school in Denmark. Engineering is a newcomer in Danish schools, and we only had fuzzy ideas about how to introduce it when we started. We therefore designed the TPD with an initial development and test phase where teachers acted as co- developers of teaching materials and didactic models. We monitored the process by teacher surveys and interviews, classroom observations and students surveys. The overall project design helped us to optimize didactic models, teaching materials and TPD activities through two iterative cycles before upscaling dissemination and teacher training.